Internal Migration, Socio-Economic Status and Remittances: Experiences of Migrant Adolescent Girl Head Porters in Ghana (African Human Mobility Review, 2021)
This paper examines the relationship between internal migration, socioeconomic status and remittances, drawing on the experiences of migrantadolescent girl head porters in the cities of Accra and Kumasi in Ghana.Through an explanatory sequential mixed methods research design involving503 individual surveys and 24 in-depth interviews, the paper established that61% of adolescents studied migrated from the north to the south to escapepoverty while 29% migrated to work and raise money for school fees. Thekayayoo business does not seem to capacitate the adolescent girls to live thekind of lives they have reason to value because only 36% of them remitted totheir families. A logistic regression model showed that older adolescents, 15-19 years, (AOR=7.32, p